Branched/linear selectivity in palladium-catalyzed allyl-allyl cross-couplings: the role of ligands. Issue 37 (16th September 2015) - Ardolino, Michael J.; Morken, James P.
Abstract: While Pd-catalyzed allyl-allyl cross-couplings in the presence of small-bite-angle bidentate ligands reliably furnish the branched regioisomer with high levels of selectivity, cross-couplings in the presence of large-bite-angle bidentate ligands give varying, often unpredictable, levels of selectivity. In a combined computational and experimental study, we probe the underlying features that govern the regioselectivity in these metal-catalyzed cross-couplings. Graphical abstract: